STRUCTURAL AND FUNCTIONAL CHARACTERIZATION OF THE APPENDIX OF PEOPLE IN AGE’s ASPEСT - Kostilenko, Yu.P.; Gryn, V.G. (World of Medicine and Biology, 2012)
Studied the microscopic structure of the appendix of people in the age aspect, starting at age 40. The functional purpose of the appendix is to periodically fence portions of the contents of the caecum. The leading role played by local limfo-epithelial association in a group of follicles and their aggregates (Peyer’s patches), where they serve as inductive and effector functions. With age, the follicular form in the appendix is gradually replaced by a diffuse type limfoepithelial association. The results obtained give grounds to say that the appendix remains active function throughout life.